Acid-promoted rapid solvent-free access to substituted 1, 4-dihydropyridines from β-ketothioamides. Issue 26 (23rd February 2016) - Li, Ming; Sun, Ke-Na; Wen, Li-Rong
Abstract : 1, 4-Dihydropyridines were synthesized via a tandem reaction of β-ketothioamides with aldehydes and β-enaminonitriles by AcOH as a promoter within 5 min. Abstract : β-Ketothioamides (KTAs) have been used as building blocks with aldehydes and β-enaminonitriles for synthesis of 1, 4-dihydropyridines in the presence of AcOH under solvent-free conditions within 5 min. This new strategy exhibits remarkable features such as high chemoselectivity, mild reaction conditions, easily available substrates, and good yields.